Penambahan Boraks dalam Bakso dan Faktor Pendorong Penggunaannya Bagi Pedagang Bakso di Kota Bengkulu - Siti Istiqomah; Mirnawati B Sudarwanto; Etih Sudarnika (Fakultas Kedokteran Hewan Universitas Gadjah Mada bekerjasama dengan PB PDHI, 2016)
The research of using borax in meatballs which was undertaken in the Bengkulu City in 2011 showed that 10% from 100 samples of meatballs containing borax. Considering the dangers of borax for the consumer if consume continuously and increasing the number of meatball traders until 2013, it is necessary to study with more meatballs samples and widely area. The aim of the study was to detect the presence of borax in meatballs, borax content after heating, storability meatballs which containing borax and determine the factors that support the meatball traders to use borax. The study was designed using cross sectional study using two types of data, they were data of meatball sample test in the laboratory and interview data to meatball traders in the BengkuluCity. Total of 160 meatball samples from traders and five meatball samples from grinders were collected and examined with qualitative test using turmeric paper. The qualitative test showed that 165 samples (100%) takenfrom meatball traders and grinders didn't contain borax. Knowledge and attitudes level of traders were at a good level. There were significant relationship between education level with knowledge, information source fromtelevision with attitude, and knowledge with attitude of traders in Bengkulu City (p < 0,05).